Dynamic changes of striatal neurotransmitter systems activity cause changes in behavioral non-convulsive disorders of depressive nature in the course of chronic seizure activity formation in kindling model of epileptogenesis - Ostapenko, I. (Journal of Education, Health and Sport, 2023)
Epilepsy is a chronic neurological disease characterized by recurrent behavioral seizures and affects approximately 1% of the global population. Epilepsy causes recurrent behavioral seizures, which are temporary behavioral changes caused by disordered, synchronized, and rhythmic activations of specific populations of neurons in the brain. Depressive disorders are one of the most common comorbid behavioral disorders in patients with epilepsy, yet they remain undiagnosed and untreated. The aim of the study is to investigate the severity of non-convulsive swimming and emotional behavior and mnemonic processes in rats with a kindling model of epilepsy under conditions of modulation of neurotransmitter systems of the caudate nuclei. It was found that in the dynamics of picrotoxin-induced kindling in rats, impaired swimming behavior, learning and memory abilities, as well as emotional dysfunctions, which are correlates of non-convulsive behavior, are recorded. It has been proven that the detected disorders of non-convulsive behaviors progressed in the dynamics of the formation of the kindling model of epilepsy and were maximal at the stages of completed kindling and postkindling. The obtained data demonstrate the key role of the striatum in the formation of non-convulsive behavioral disorders. On the 18th day, the pro-convulsive role of striatum is noted, which is confirmed by the enhancement of GABAergic and inhibition of dopaminergic neurotransmission of striatum along with the inhibition of its cholinergic mediation. The completion of the formation of kindling is confirmed by the enhancement of cholinergic and dopaminergic neurotransmission of striatum along with the inhibition of GABAergic mechanisms. In the postkindling stage, activation of cholinergic and dopaminergic neurotransmission of striatum and inhibition of its GABAergic activity are observed. The author considers the data obtained to be an experimental basis for the feasibility of testing clinical diagnostic effects in terms of dynamic monitoring of the behavior of patients with epilepsy during interictal periods, as well as possible corrective pharmacological effects in the case of modulation of the activity of certain neurotransmitter systems and intrastriatal neurotransmission.